Perubahan Kebijakan Turki: Open Door Policy Menjadi Border Wall Project Tahun 2015-2022 - Abidin, Wilda Daffania; Wibowo, Prihandono (Global and Policy Journal of International Relations, 2024)
This research aims to analyze changes in Turkish foreign policy regarding the Open Door Policy and identify the factors that caused the change from the Open Door Policy to the Border Wall Project. To achieve this research objective, this research focuses on the change in the direction of Turkey's foreign policy from the Open Door Policy to the Border Wall Project towards Syrian and Afghan immigrants since the conflict caused by the Arab Spring in Syria until the takeover of power by the Taliban in Afghanistan. This research uses an explanatory qualitative approach method through literature study by analyzing data based on Joakim Eidenfalk's theory of foreign policy change. The main question of this research is why did Turkey implement changes to the Open Door Policy to become the Border Wall Project in 2015-2022? The research focuses on analyzing the factors that drive changes in Türkiye's Open Door Policy. In this research, it appears that the change from the Open Door Policy to the Border Wall Project on the southern and eastern borders was due to the intensity of terrorist attacks in Turkey, changes in the direction of public opinion towards immigrants, the influence of the media on public opinion, the increase in illegal smuggling, securing Turkey's national security and increasing activities of militants and terrorist organizations near the border.Keywords: Open Door Policy, Border Wall Project, TürkiyePenelitian ini bertujuan menganalisis perubahan kebijakan luar negeri Turki terkait Open Door Policy dan mengidentifikasi faktor-faktor yang menyebabkan terjadinya perubahan dari kebijakan Open Door Policy menjadi Border Wall Project. Untuk mencapai tujuan penelitian tersebut, penelitian ini berfokus pada berubahnya arah kebijakan luar negeri Turki dari kebijakan Open Door Policy menjadi Border Wall Project terhadap para imigran Suriah dan Afghanistan sejak konflik akibat Arab Spring di Suriah hingga pengambil alihan kekuasaan oleh Taliban di Afghanistan. Pertanyaan utama penelitian ini adalah mengapa Turki menerapkan perubahan terhadap kebijakan Open Door Policy menjadi Border Wall Project pada tahun 2015-2022?. Penelitian berfokus pada analisis faktor-faktor yang mendorong perubahan kebijakan Open Door Policy Turki. Dalam penelitian ini, terlihat bahwa perubahan Open Door Policy menjadi Border Wall Project di perbatasan selatan dan timur adalah karena intensitas serangan terorisme di Turki, perubahan arah opini publik terhadap imigran, pengaruh media terhadap opini publik, meningkatnya penyelundupan ilegal, pengamanan keamanan nasional Turki dan peningkatan aktivitas militan dan organisasi teroris di dekat perbatasan. Kata Kunci: Open Door Policy, Border Wall Project, TurkiDOI: https://doi.org/10.33005/jgp.v12i01.4279